PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL SEKRETARIAT DAERAH KABUPATEN KARAWANG - Subhan Agustian subhan; Solehudin Solehudin; Banuara Nadeak (Universitas Djuanda Bogor, 2022)
This study aims to examine and analyze the effect of motivation and work environment on the performance of Civil Servants at the Regional Secretariat of Karawang Regency. This study uses descriptive and verification methods, namely: collecting, presenting, analyzing and testing hypotheses and making conclusions and suggestions. Samples were collected using non-probability sampling technique with purposive sampling as many as 134 people. The analytical technique used is the technique of scale range analysis and path analysis with the help of the Method of Successive Interval (MSI), the Microsoft Excel 2013 computer program and the SPSS version 21 application. Based on the results of the analysis that has been done this research proves that the correlation coefficient between the motivation variable and the work environment is obtained a value of 0.432 which means it has a fairly strong, positive and significant correlation level between motivation and the work environment. The partial effect of motivation on employee performance is 0.210, smaller than the work environment, which is 0.257. So it can be stated that the work environment contributes more to employee performance than motivation. The simultaneous influence of motivation and work environment on employee performance is 46.7% while the remaining 53.3% is another variable that was not examined.